Nolo's quick LLC : all you need to know about limited liability companies - Mancuso, Anthony (Nolo, 2023)
If you run your own business as a sole proprietorship or partnership, you've probably heard of the advantages of limited liability companies--especially the way an LLC can protect personal assets from business debts. LLC expert Anthony Mancuso clearly explains how to decide whether an LLC is right for you. Learn: the unique legal features of LLCs, including limited personal liability for owners; who should--and who shouldn't--form an LLC; when to choose an LLC instead of a corporation, partnership, or other business form; how LLCs are taxed; how to manage multiple-owner LLCs, and why an LLC can be the right choice even for a debt-troubled business